Enhancing psychological health and cognitive inhibition in college students: insights from mindfulness training and high-intensity interval training - Bao, Yintu; Sun, Jianqian; Zhang, Xiaochuan (Frontiers in Psychology, 2025)
BackgroundThis study aimed to examine the effects of mindfulness training (MT) and high-intensity interval training (HIIT) on enhancing psychological health and cognitive inhibition in college students.MethodsA total of 132 undergraduates were recruited and randomly assigned to three groups: MT group, HIIT group, and control group. Both the MT and HIIT groups received training twice a week for 6 weeks, with each session lasting 1 h. The control group did not undergo MT or HIIT training during the experimental period. The Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI), Stop Signal tasks, and Flanker tasks were assessed at baseline, at 6 weeks (post-test), and 6 weeks after the end of the intervention (follow-up).ResultsBoth MT and HIIT were effective in alleviating depression and anxiety in college students, with MT showing a significant improvement in psychological health after intervention. Both MT and HIIT effectively improved the response inhibition accuracy of college students, with similar effects. However, neither MT nor HIIT affected the response inhibition reaction time. MT was more effective than HIIT in improving interference inhibition accuracy, but neither MT nor HIIT had an effect on the interference inhibition reaction time.ConclusionWithin-group analyses demonstrated significant pre-post reductions in depression and anxiety scores following both MT and HIIT interventions. While between-group comparisons suggested a trend toward greater symptom improvement in the MT group at post-test, the differences did not reach statistical significance at follow-up, possibly due to the limited sample size and intervention duration. These preliminary findings warrant replication in larger-scale trials with extended observation periods.